Open Science and Open Access Scientific Publishing: an essential combination. An analysis of the first 4 years of JBP activity - Sellitti, Francesco Paolo; Alemanno, Antonio; Camoni, Luca; Coriasco, Mario Gino; Gennari, Luciana; Giacomelli, Manuela; Gnagnarella, Patrizia; Piedimonte, Alessandro; Vernone, Annamaria; Rabellino, Sergio; et al. (Journal of Biomedical Practitioners, 2021)
In July 2017, the Journal of Biomedical Practitioner (JBP) starts publications with its first number. Since its debut JBP would offer itself as a meeting place to health professionals, free to all and Open Access, without prejudices for experience exchanging between people that work in Biomedical Sciences with various purposes from welfare, diagnostic-therapeutic, rehabilitation and prevention, to the fields of basic and clinical research. JBP it’s a six-monthly publication, with double-blind peer review, written in Italian and English language. This editorial aims to analyze in deep the journal path in these 4 years, reporting the poster contents shown at 2° Congresso Nazionale della Federazione Nazionale Ordini dei Tecnici Sanitari Radiologia Medica e delle Professioni Sanitarie Tecniche, della Riabilitazione e della Prevenzione (FNO TSRM e PSTRP) that took place in Rimini on 19-21 november 2021. The improvement of quality standards offered will be highlighted, noting the fundamental role of the contribution of the auditors. The metadata analysis on the OJS/PKP platform, which is used by the journal and in turn it’s hosted by Sistema di Riviste Open Access (SIRIO@Unito) of the University of Turin, shows much interesting information about the article submitted: we received 90 article proposals and the 57% was published, of which the 16% was written in the two languages. The mean time needed was 62 days for the revision process and 110 days to get the article published. In each year were published a mean of 13 papers and 60% of them were written by authors from different professional areas. The fast access to the contents and the indexing of JPB on the main directories of Open Access Journals are the best reasons to choose this journal for publishing in the Biomedical Science areas.